2023
DOI: 10.21134/eurjhm.2022.49.9
|View full text |Cite
|
Sign up to set email alerts
|

Normative data of the start in the 50 m events at the 2021 LEN European Championships and understanding its relationship with the final race

Abstract: This study aimed to: (i) present normative data of the variables related to the start in the four swim strokes by tier and sex, and; (ii) understand the relationship between the 15th meter mark time and the final race time of the male and female swimmers competing in the four 50 m events at the 2021 European Championships. Participants were all male and female swimmers who competed in the 50 m events at the 2021 LEN European Championships held in Budapest. The official race times and block times were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…This keyword aspect is very important for this type of analysis. For example, based on the articles retained for analysis, it was found that some articles of the present research group were not selected for analysis ( 102 , 103 ). This occurred because the selection of words in the title and keywords of the articles were not related to the chosen search strategy on this topic (please refer to the subsection “Data source and search strategy”).…”
Section: Discussionmentioning
confidence: 99%
“…This keyword aspect is very important for this type of analysis. For example, based on the articles retained for analysis, it was found that some articles of the present research group were not selected for analysis ( 102 , 103 ). This occurred because the selection of words in the title and keywords of the articles were not related to the chosen search strategy on this topic (please refer to the subsection “Data source and search strategy”).…”
Section: Discussionmentioning
confidence: 99%